Tinjauan Statistik Asuhan Kesehatan Di RSUD PROF. DR. MA Hanafiah SM Batusangkar Periode 01-31 Januari 2019 - Laifatul Husna (AKADEMI PEREKAM DAN INFORMASI KESEHATAN (APIKES) IRIS PADANG, 2022)
The medical record must contain sufficient data to identify the patient. This is because medical records are a source of data used in processing statistical data on hospital care. Data collection at Prof. Hospital. Dr. MA. Hanafiah Batusangkar for the January 1-31 2019 period is secondary data, data obtained from 664 patients went home, with a total of 171 beds. Data processing using Microsoft Office Excel After processing the data, statistical processing is carried out with the following results: the results of the BOR obtained are 44.75%. BOR is not efficient because the efficiency level of BOR is 60-85%. Then the BTR result is 4 times. BTR is not efficient because the calculation of BTR is done once a year with an efficiency level of 40-50 times. The result of IT is 4 days, the value of IT is not efficient because IT efficiency is 1-3 days.